Detecting Changes in European Shoreline Evolution Trends Using Markov Chains and the Eurosion Database - Le Cozannet, Gonéri; Oliveros, Carlos; Brivois, Olivier; Giremus, Audrey; Garcin, Manuel; Lavigne, Franck (Frontiers in Marine Science, 2020)
European coastal databases contain information on the evolution of European shorelines in the 1990s and the 1980s. We investigate if a shift toward erosion has been observed between these two periods, as it could be expected as a consequence of contemporary sea-level rise or changing coastal management practices. We select comparable European coastal sites, consider their state transitions as the parameters of a discrete-time Markov chain, and analyze their steady states in order to reveal underlying changes in shoreline evolution trends. The results suggest that European coastal wetlands and small beaches have initiated a shift toward erosion, which attenuates previous optimistic statements. Our results should be interpreted with caution due to the limited number of observations and presumed errors in the database. However, they suggest that the impact of contemporary sea level rise along European coastlines in the 90s may be more important than previously thought. Our results suggest that more research is needed to quantify the morphodynamics of muddy coasts and to develop data models able to represent coastal morphodynamic changes adequately.